FA’ALIYATU ISTIRAATIJIYAT RIWAYATI AL-QHOSHAHI AR_RAQMIYYAH LITARQIYATI QUDRATU AT-TULLAB ‘ALA MAHAARATI AL-KALAM - Ellisa Qudratul Jannah; Nurul Wahdah; Yulia Rahmah (El-Tsaqafah : Jurnal Jurusan PBA, 2021)
This study aims to determine the effectiveness of the Digital Storytellingstrategy in improving students’ speaking skills. This study uses a quantitativeresearch method of experimental type or true experimental design using a pretestposttestcontrol group design. Participants in the study were class VIII participantsat an Integrated Islamic Junior High School (SMP IT) in Palangka Raya City. . Fromthis study found the following results: 1. participants in the control class showed anincrease in speaking ability seen from the average value of the pretest and posttestresults, namely the pretest average value of 77.02 increased to 92.64 in the averagevalue. average posttest results. So it can be concluded that participants’ speakingskills can improve even if they do not use digital story telling (DST) strategies.2. Participants from the experimental class showed an increase in speaking abilityseen from the average value of the pretest and posttest results, namely the averagepretest value of 76.02, an increase in the average value of the posttest results to94.41. So it can be concluded that the digital story telling (DST) strategy can improveparticipants’ speaking skills. 3. The comparison of the posttest average value of theexperimental class and the control class using the Mann Whitbey test because thedata is not normally distributed, a significance value of 0.084 is obtained, which isgreater than 0.05, so there is no significant difference in learning outcomes betweenthe experimental class participants who learn to use a digital story telling (DST)strategy with control class participants who do not use this strategy. However,because the posttest average value of the experimental class was higher, the digitalstory telling (DST) strategy was more effective for the participants in this study.